2017
DOI: 10.1016/j.molimm.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

C1q as an autocrine and paracrine regulator of cellular functions

Abstract: Most of the complement proteins in circulation are, by and large, synthesized in the liver. However data accumulated over the past several decades provide incontrovertible evidence that some if not most of the individual complement proteins are also synthesized extrahepatically by activated as well as non-activated cells. The question that is finally being addressed by various investigators is: are the locally synthesized proteins solely responsible for the myriad of biological functions in situ without the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 99 publications
1
29
0
Order By: Relevance
“…Cluster CM1 expressed upregulated levels of phagocytic receptors CD36 (SCARB3), SCARB2, CD68, CD163, NR1H3 (LXR), and GPNMB and cluster CM4 expressed VSIG4, MSR1, CD163, MERTK, STAB1 and CD209. Cells in CM1 and especially CM4 had upregulated expression of C1Q, which not only acts as an opsonin for phagocytosis but also promotes apoptotic cell clearance by enhancing the expression of MERTK (in the presence of other molecules, such as HMGB1) and its soluble ligand GAS6 10,11 . Clusters CM1 and CM4 also expressed the highest levels of the sialic acid binding immunoglobulin lectin CD169 (SIGLEC1), an endocytic receptor that has been detected on infiltrating macrophages in a variety of human renal inflammatory diseases and that is associated with a phagocytic and reparative phenotype 12 .…”
Section: Classification and Annotation Of Myeloid Cell Clusters Reveamentioning
confidence: 99%
“…Cluster CM1 expressed upregulated levels of phagocytic receptors CD36 (SCARB3), SCARB2, CD68, CD163, NR1H3 (LXR), and GPNMB and cluster CM4 expressed VSIG4, MSR1, CD163, MERTK, STAB1 and CD209. Cells in CM1 and especially CM4 had upregulated expression of C1Q, which not only acts as an opsonin for phagocytosis but also promotes apoptotic cell clearance by enhancing the expression of MERTK (in the presence of other molecules, such as HMGB1) and its soluble ligand GAS6 10,11 . Clusters CM1 and CM4 also expressed the highest levels of the sialic acid binding immunoglobulin lectin CD169 (SIGLEC1), an endocytic receptor that has been detected on infiltrating macrophages in a variety of human renal inflammatory diseases and that is associated with a phagocytic and reparative phenotype 12 .…”
Section: Classification and Annotation Of Myeloid Cell Clusters Reveamentioning
confidence: 99%
“…These include the recognition of pathogen- and danger-associated molecular patterns, phagocytosis, angiogenesis, apoptosis and induction of cytokines or chemokines that are important in modulating the inflammatory response. The functional convergence between C1q and TNF-α in turn is attributed to their shared genetic ancestry [ 18 ]. Moreover, studies have shown that C1q can play an important role in other diseases, including autoimmunological diseases [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complement factors help induce inflammation against microbial invasion, and cross‐react with toll‐like receptors (TLRs), inflammasomes, and the acute‐phase protein (or C‐reactive protein, C‐RP). C1q partially shares the same role as TNF‐α …”
Section: Complement Factors and Inflammationmentioning
confidence: 99%
“…C1q partially shares the same role as TNF-α. 27 Innate immune cells (neutrophils macrophages, dendritic cells…”
Section: Complement Fac Tor S and Infl Ammationmentioning
confidence: 99%